The active brain: relationships between physical activity, fitness, cognitive performance and brain structure in young adolescents - Wassenaar, TM (2021)
Governmental, scientific and public health communities have become increasingly interested in the potential of physical activity to promote neurocognitive health across the lifespan. While research in adults has advanced rapidly in the past 20 years, much less is known about the effects of a physically active lifestyle on cognitive and brain health in young people, especially adolescents. Using magnetic resonance imaging (MRI) and cognitive data from the Fit to Study cluster randomised controlled trial, this thesis therefore examined relationships between neurocognitive health and markers of physical activity and cardiorespiratory fitness in this age group. A cross-sectional study involving baseline Fit to Study data showed that higher levels of physical activity and fitness are associated with superior performance on domain-specific cognitive assessments (working memory, cognitive flexibility, inhibitory control, visual memory and processing speed) in a large sample of young British adolescents (n = 16,017), but that relationships are small and explain less than 10% of the variance in cognitive outcomes. It also showed that relationships may be stronger in females compared to males and that a physically active lifestyle is linked with more favourable cognitive outcomes. In a sub-sample of adolescents (n = 61), however, no significant relationships between markers of a physically active lifestyle and volumes or multi-modal MRI markers of tissue (micro)structure in the anterior hippocampus were observed.